Wet Load Study of Gross Pollutant Traps; Kemensah River, Malaysia - Zahari N.M.; Sidek L.M.; Basri H.; Md Said N.F.; Md Noor M.S.F.; Jajarmizadeh M.; Zainal Abidin M.R.; Mohd Dom N. (Institute of Physics Publishing, 2023)
Catchments; Pollution; Rivers; Continuous deflective separations; Drainage systems; Government agencies; Gross pollutants; Malaysia; Rainy seasons; Residential areas; River systems; River pollution; catchment; performance assessment; policy implementation; pollution control; research method; river system; seasonality; separation; solid waste; water management; water pollution; water quality; wetting; Malaysia